SYNERGISING NEW MEDIA POTENTIAL AND BUSINESS EDUCATION FOR ECONOMIC GROWTH IN NIGERIA - Ito, Fidelia Mamezi; Ivwighren, Hannah Emuobosa (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
The integration process of the new media technologies to enhance teaching and learning of business is a revolutionary approach to producing business leaders. Therefore, study’s objective is to establish the effectiveness of the incorporation of new media to provide an engaging, exciting, and Versatile approach to business education. It is a mixed-method study combining survey and key information interview. The study targets 300 final year students of Ajuru University of Education, Port Harcourt, and interviews of key informants who are media technology specialists, entrepreneurs and educational administrators from Port Harcourt for insights of valuable information on the integration of new media with business education and how to maintain academic integrity in an online system are touched on, thus presenting a fair viewpoint of the efficacy of adopting it. Technological Diffusion Theory of how innovations spread in a society or an organization was used to explain the manner in which new media technologies were adopted and implemented in business environments. Mean output was added in the data summary of the survey and the inferential statistics that were employed utilizing Spearman Rank on Software app STATA 15. zero to attempt a hypothesis to discover interconnection among the variables. The findings confirm how new media when appropriately adopted and integrated into teaching and learning practices in business education has a big potential of delivering on its promise. It also recommends media organization should collaborate with universities, vocational training centers, and businesses to establish internship programs and collaborative projects focusing on new media applications in business.